Determinan Tingkat Kepuasan Mahasiswa Vokasi Mengikuti Kuliah Daring di Masa Pandemi Covid-19 - Supardi, Supardi; Ashari, Sidiq (E-Jurnal Akuntansi, 2021)
This article investigates the relationships between social presence, cognitive absorption, and satisfaction of vocational college students in online learning. A hypothesized structural equation model was developed to study these critical variables that may influence interaction in online learning environments. Data was obtained through questionnaires from 448 students of vocational college at Yogyakarta.  Data  was analyzed by Structural Equation Modelling - Partial Least Square (PLS) using Smart PLS 2.0. The results of this research shows that the social presence and cognitive absorption of  vocational college students is impact satisfaction directly. Keywords: Social Presence; Cognitive Absorption; Student Satisfaction .